Karakteristik Susu Kerbau Sungai dan Rawa di Sumatera Utara - Damayanthi, Evy; Yopi, .; Hasinah, Hasanatun; Setyawardani, Triana; Rizqiati, Heni; Putra, Salwa (Jurnal Ilmu Pertanian Indonesia, 2014)
The objective of this research was to investigate the characteristics and differences in quality milk of Water andSwamp buffalo milk in North Sumatera. This research was conducted used complete random design used 30buffalo from three breeding farm in North Sumatera. Buffalo milk were collecting from lactating buffaloes on threetraditional farms located at Patumbak, Lubuk Pakam, and Siborong-borong with extensive farming system. Theresult of this research shown milk production per day for Swamp buffalo is 1 1.5 l and Water buffalo is 6 8 l withquality of Swamp and Water buffalo sequentially are for protein 5.14 ± 0.37% and 4.68 ± 0.41%, fat content 7.52 ±0.98% and 4.13 ± 0.73%, non-fat dry matter (NFDM) 10.61 ± 0.78% and 11.5 ± 0.86%, moisture 81.87 ± 2.26% and80.33 ± 2.33%, milk density 1.030 and 1.036, and then Total Plate Count (TPC) 3.79 x 106 and 5.08 x 105, shownindicated that there ware significant difference in protein, fat content and NFDM (P